Adolescent religiosity and pre-marital sexual behavior: The mediating role of pre-marital sexual attitude - Mira Sekar Arumi; Nova Faradilla (Institut Agama Islam Negeri Langsa, 2023)
Pre-marital sex before marriage in adolescents is a severe problem associated with increased transmission of sexually transmitted diseases, having more than one partner, and early pregnancy. Even though Indonesia is considered a society with high religious values, free-sex behavior is considered increasingly concerning. This study investigates the relationship between religiosity and attitudes toward pre-marital sexual behavior with pre-marital sexual behavior in adolescents. Respondents of this study were 200 adolescents aged 10-19 years old, selected through a purposive sampling technique, with criteria: have religion, not married, and currently dating. Data were analyzed using a linear regression method. The results showed that pre-marital sexual attitude fully mediates the effect between religiosity and pre-marital sexual behavior. The present study findings contribute to pre-marital sexual research by explaining that religiosity does not decrease pre-marital sexual behavior if the person is permissive or has a supportive attitude towards it. With this outcome, it is expected that the relevant parties will focus more on changing adolescents’ thoughts, attitudes, and perspectives regarding pre-marital sexual behavior and not only rely on religious teachings as the only framework for preventing pre-marital sexual behavior